Immediate stress alters social and object interaction and recognition memory in nearly isogenic rat strains with differing stress reactivity. (2nd November 2021) - Schaack, Alice K.; Mocchi, Madaline; Przybyl, Katherine J.; Redei, Eva E.
Abstract: Stress prior to learning and recall is known to affect both processes depending on the learning paradigm, the sex of the animal, and their reactivity to stress. Male and female animals of the inbred Wistar-Kyoto More Immobile (WMI) and Less Immobile (WLI) strains were tested in the modified novel object and spatial recognition paradigm and in the social interaction-recognition paradigm immediately after a 30 min restraint stress. The WMI strain shows enhanced stress reactivity compared to its near isogenic WLI control and thus, represents a genetically stress-susceptible rodent model. Without stress, there were no strain differences in social or object recognition, but there were sex differences in both types of investigation. Immediate stress generally increased object investigation, but decreased social interaction in all groups, except the WMI males, who exhibited increased aggression toward the juveniles. While stress increased plasma corticosterone and decreased testosterone levels in WLI males as expected, it increased testosterone in the aggressive WMI males, despite elevated levels of corticosterone. Stress generally decreased recognition, except the spatial recognition of WMI females, which paradoxically improved after stress. The strain-specific effects of immediate stress indicate that stress unlocks the vulnerability encoded by the stable genetic differences between WLIs and WMIs to result in the observed phenotypes.